2008
DOI: 10.1557/proc-1069-d04-03
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Conditions and Substrate Properties on Formation of Interfacial Dislocations and Dislocation Half-loop Arrays in 4H-SiC(0001) and (000-1) Epitaxy

Abstract: Formation of interfacial dislocations (IDs) and dislocation half-loop arrays (HLAs) and their appearance in 4H-SiC epi-wafers are investigated by X-ray topography and KOH etching analysis. Synchrotron reflection X-ray topography demonstrates the ability to image IDs and HLAs simultaneously and reveal their densities as well as spatial distributions in the epi-wafers. The vertical location of IDs in the epi-wafer is also examined by this technique. The influence of wafer warp, in-situ H2 etching prior to epitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…According to current understanding, the screw oriented BPD in the epilayer ͑marked BC͒ undergoes sideways glide under the action of lattice mismatch stress 13 leaving a trailing interfacial dislocation ͑ID͒ at or near the substrate/epilayer interface ͑marked AB͒ and trails of dislocation configurations known as HLAs ͑the array of dots along DC͒ in the epilayers. [12][13][14][15][16] The motion of the ID toward the interface has evidently been impeded, forcing it to settle at some 40 m above the interface. This particular image was chosen since if the dislocation were in fact at the interface, it would be invisible on the UVPL image because its luminescence would be quenched by the adjacent heavily doped substrate.…”
mentioning
confidence: 99%
“…According to current understanding, the screw oriented BPD in the epilayer ͑marked BC͒ undergoes sideways glide under the action of lattice mismatch stress 13 leaving a trailing interfacial dislocation ͑ID͒ at or near the substrate/epilayer interface ͑marked AB͒ and trails of dislocation configurations known as HLAs ͑the array of dots along DC͒ in the epilayers. [12][13][14][15][16] The motion of the ID toward the interface has evidently been impeded, forcing it to settle at some 40 m above the interface. This particular image was chosen since if the dislocation were in fact at the interface, it would be invisible on the UVPL image because its luminescence would be quenched by the adjacent heavily doped substrate.…”
mentioning
confidence: 99%
“…It suggests that during the homoepitaxial growth on those substrates, the stress (compressive or tensile) for the epilayers may be different. In fact, after the growth, the misfit dislocations generally exist in the central part of the epi-wafers in the Si-face case, whereas they locate locally at some edge parts of the epi-wafers in the C-face one [20], as schematically illustrated in Fig. 5.…”
Section: Comparison Between C-and Si-facementioning
confidence: 98%
“…It has been shown that when the substrates are sliced from the same bulk, the Si-face substrates are concave while the C-face ones are convex towards the respective growth faces [20]. It suggests that during the homoepitaxial growth on those substrates, the stress (compressive or tensile) for the epilayers may be different.…”
Section: Comparison Between C-and Si-facementioning
confidence: 99%
“…(2) Occurrence of interfacial dislocation It is often observed that L-shaped or reverse L-shaped interfacial dislocation occurs on the interface between the epitaxy film and the bare substrate of 4H-SiC wafers even though a homo-epitaxy film is grown [8,[20][21][22][23]. Figure 5 shows one of the examples of the interfacial dislocation observed on the Si surface of 4H-SiC wafer appeared after epitaxy film growth.…”
Section: Changes Of Dislocation Structure Associated With Epitaxy Filmentioning
confidence: 99%
“…(3) Formation of half-loop dislocation array When a terminal end of an interfacial dislocation glides on the epitaxy film surface, sometimes the terminal end also leaves multiple tiny half-loop dislocation arrays [20][21][22][23]. Figure 7(a) shows this case.…”
Section: Changes Of Dislocation Structure Associated With Epitaxy Filmentioning
confidence: 99%